Development and validation of the Emergency Department Assessment of Chest pain Score and 2 h accelerated diagnostic protocol. (15th January 2014) - Than, Martin; Flaws, Dylan; Sanders, Sharon; Doust, Jenny; Glasziou, Paul; Kline, Jeffery; Aldous, Sally; Troughton, Richard; Reid, Christopher; Parsonage, William A; Frampton, Christopher; Greenslade, Jaimi H; et al.
Abstract Objective Risk scores and accelerated diagnostic protocols can identify chest pain patients with low risk of major adverse cardiac event who could be discharged early from the ED, saving time and costs. We aimed to derive and validate a chest pain score and accelerated diagnostic protocol (ADP) that could safely increase the proportion of patients suitable for early discharge. Methods Logistic regression identified statistical predictors for major adverse cardiac events in a derivation cohort. Statistical coefficients were converted to whole numbers to create a score. Clinician feedback was used to improve the clinical plausibility and the usability of the final score (Emergency Department Assessment of Chest pain Score [EDACS]). EDACS was combined with electrocardiogram results and troponin results at 0 and 2 h to develop an ADP (EDACS‐ADP). The score and EDACS‐ADP were validated and tested for reproducibility in separate cohorts of patients. Results In the derivation (n = 1974) and validation (n = 608) cohorts, the EDACS‐ADP classified 42.2% (sensitivity 99.0%, specificity 49.9%) and 51.3% (sensitivity 100.0%, specificity 59.0%) as low risk of major adverse cardiac events, respectively. The intra‐class correlation coefficient for categorisation of patients as low risk was 0.87. Conclusion The EDACS‐ADP identified approximately half of the patients presenting to the ED with possible cardiac chest pain as having low risk of short‐term major adverse cardiac events, with high sensitivity. This is a significant improvement on similar, previously reported protocols. The EDACS‐ADP is reproducible and has the potential to make considerable cost reductions to health systems.